Journalists and Communicators' Perceptions of Their Graduate Training in Environmental Reporting: An Application of Knowledge-Based Journalism Principles - Takahashi, Bruno; Parks, Perry (Frontiers in Environmental Science, 2018)
This study explores the educational and post-graduation experiences of graduates of a master’s program with a focus on environmental journalism. The study uses the framework of knowledge-based journalism to qualitatively examine how the competencies of journalistic skills, general and content-specific knowledge, learning communication theory, and developing journalistic values allowed graduates to develop a niche in their professional careers. Results show respondents placed disproportionate emphasis on the importance of journalistic skills and were ambivalent about the value of theory courses. The responses suggest scholars’ idealistic conception of knowledge-based journalism is problematic when applied to the changing realities of journalism and the media industry in the U.S.